1971
DOI: 10.1002/jlac.19717520121
|View full text |Cite
|
Sign up to set email alerts
|

über zweistufige Redoxsysteme, VII. Polarographie und Spektroskopie heterocyclischer Azine und ihrer höheren Oxydationsstufen

Abstract: Die Polarographie der heterocyclischen Redoxsysteme 6-10,14 und 15 zeigt reversible zweistufige Einelektroneniibergange mit Semichinonbildungskonstanten K M 107-1010 (6-10) bzw. -104 (14) und 120 (15) [Abbildung 61. Der SubstituenteneinfluD auf K und die Lage der Potentiale werden besprochen. Die Elektronenspektren von 6-10, 14 und 15 in ihren Oxydationsstufen RED, SEM und OX werden verglichen (Tabelle 3). Two-step Redox Systems, VII 1). Polarography and Spectroscopy of Heterocyclic Azines and their Higher Oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1971
1971
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In addition, several electron-rich tetrakis- and even hexakis­(guanidino) benzene systems such as 331 and 332 were prepared by the Himmel group , and used as redox-active compounds with multistage redox behavior or as ligands for the preparation of coordination polymers. Another peculiar example is the urea azine 333 , which resembles the heterocyclic 2,2′-azines already described by Hünig and co-workers between 1964 and 1971. 333 was obtained from the reaction of 2-chloro-1,3-dimethylimidazolium chloride and hydrazine hydrate, and it can be formally perceived as the lightest N-heterocyclic group 15 dicarbene–dielement complex. , Similar to Hünig’s azines, 333 represents a two-stage redox systems, which can be reversibly oxidzed to the corresponding radical cation and dication, and its reactivity toward ZnCl 2 , CoCl 2 , and CuCl 2 was also studied. , The latest additions to the family of chelating imidazolidine ligands stems from the Eisen group, who introduced imidazolidin-2-imine-aryloxide ligands of type 334 , which were used for the preparation of Ni­(II) and Pd­(II) complexes [( 334 )­M­(PPh 3 )­R] (M = Ni, R = Ph; M = Pd, R = Me) …”
Section: N-heterocyclic Carbene Adducts Of Group 15 Elementsmentioning
confidence: 99%
“…In addition, several electron-rich tetrakis- and even hexakis­(guanidino) benzene systems such as 331 and 332 were prepared by the Himmel group , and used as redox-active compounds with multistage redox behavior or as ligands for the preparation of coordination polymers. Another peculiar example is the urea azine 333 , which resembles the heterocyclic 2,2′-azines already described by Hünig and co-workers between 1964 and 1971. 333 was obtained from the reaction of 2-chloro-1,3-dimethylimidazolium chloride and hydrazine hydrate, and it can be formally perceived as the lightest N-heterocyclic group 15 dicarbene–dielement complex. , Similar to Hünig’s azines, 333 represents a two-stage redox systems, which can be reversibly oxidzed to the corresponding radical cation and dication, and its reactivity toward ZnCl 2 , CoCl 2 , and CuCl 2 was also studied. , The latest additions to the family of chelating imidazolidine ligands stems from the Eisen group, who introduced imidazolidin-2-imine-aryloxide ligands of type 334 , which were used for the preparation of Ni­(II) and Pd­(II) complexes [( 334 )­M­(PPh 3 )­R] (M = Ni, R = Ph; M = Pd, R = Me) …”
Section: N-heterocyclic Carbene Adducts Of Group 15 Elementsmentioning
confidence: 99%
“…In order to prepare the symmetrical azino-DSeDAF 1, we followed Hünig's strategy which consists of the reaction of quaternary heterocyclic salts with a half equivalent of hydrazine in a basic medium (Scheme 1) [3]. First, we prepared 3-methyl-2-methylthio-benzoselenazolium salt 3 from 2-methylthio-benzoselenazole 2 [6] with a new one-step approach in 91% yield.…”
Section: Synthesis and Electrochemical Studiesmentioning
confidence: 99%
“…Among the numerous variations realized on the fulvalene skeleton, the insertion of a conjugated spacer group such as an azino one between the two heterocyclic cores gave rise to an interesting family of compounds known as heterocyclic azines [2]. Hünig et al developed this strategy some years ago and showed that these derivatives present two monoelectronic oxidation waves with excellent reversibility [3]. Additionally, the presence of an azino spacer group increases the window potential stability of the cation radical species.…”
Section: Introductionmentioning
confidence: 99%